2015
DOI: 10.1007/s00330-015-3959-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain herniations into the dural venous sinus or calvarium: MRI findings, possible causes and clinical significance

Abstract: • Brain herniations into the DVS are more common than previously assumed. • The most frequent locations are the transverse sinus. • These herniations are incidental findings. • The relationship between brain herniation into DVS and headache is uncertain. • High-resolution MR sequences are most useful in detection of brain herniations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 7 publications
5
70
7
Order By: Relevance
“…They are functionally and histologically related to arachnoid villi, differing only in size and complexity, providing a route for cerebral spinal fluid (CSF) resorption into the bloodstream . Frequently seen on imaging, AGs are considered normal anatomic structures, though rare cases have been reported that indirectly implicate AGs with symptoms such as headache, tinnitus, CSF otorrhea, and intracranial venous hypertension …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are functionally and histologically related to arachnoid villi, differing only in size and complexity, providing a route for cerebral spinal fluid (CSF) resorption into the bloodstream . Frequently seen on imaging, AGs are considered normal anatomic structures, though rare cases have been reported that indirectly implicate AGs with symptoms such as headache, tinnitus, CSF otorrhea, and intracranial venous hypertension …”
Section: Introductionmentioning
confidence: 99%
“…Recently, herniation of brain parenchyma into the dural venous sinuses and calvarium have been reported, sometimes referred to as occult encephaloceles, as the herniation does not extend through the outer cortex of the calvarium or skull base . While it remains to be proven, the association of the herniation with presumed preexisting AGs has been suggested in prior reports.…”
Section: Introductionmentioning
confidence: 99%
“…Brain parenchyma herniations with surrounding CSF into the DVS and/or calvarium have a prevalence of 0.32% and were encountered more frequently in posterior inferior parts of the intracranial cavity [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Battal and Castillo [4] concluded that herniations of brain parenchyma into arachnoid granulations can occur spontaneously or as a result of increased intracranial pressure. Battal et al [12] in another study referred that the herniations were incidentally detected in all patients and the majority occurred spontaneously, but few were associated with masses that presumably could have increased intracranial pressure. It was suggested that the underlying giant arachnoid granulation might be a predisposing factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation